Associations between HEXACO personality traits, substance use disorders, and behavioral addictions: a protocol for a comprehensive systematic review and meta-analysis - Farangis Sharifibastan; Eilin Kristine Erevik; Katharina Teresa Enehaug Morken; Ståle Pallesen (Systematic Reviews)
Abstract Background While research has explored the connection between addiction and personality, no systematic study has examined how substance use disorders (SUD) and behavioral addictions specifically relate to the HEXACO model of personality. This systematic review and meta-analysis aim to fill this gap by investigating the association between HEXACO personality traits and various addictions, including illegal substances (e.g., narcotics and cannabis) and behavioral addictions (e.g., gambling, gaming, social media addiction, and compulsive sexual behavior disorder) across different populations. Methods The protocol is in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) statement. Searches will be conducted in databases including APA PsycINFO (Ovid), MEDLINE (Ovid), ProQuest, Web of Science, CINAHL, Wiley Online Library, and Google Scholar. Empirical studies published as full papers in peer-reviewed journals or as full dissertations, in English, other European languages, or Persian, investigating the association between HEXACO personality traits and addictive disorders are eligible. Two reviewers will independently screen all citations and full-text articles, and extract data using the Covidence software. They will further assess the risk of bias and quality of the studies using the Newcastle–Ottawa Scale (NOS) for longitudinal and cohort studies, an adapted version of the NOS for cross-sectional studies. Publication bias will be evaluated using funnel plots, Egger’s test, and trim and fill analysis. In addition to a narrative summary, meta-analyses will be conducted if data are sufficient. Random effects models will be used to pool effect sizes. Subgroup analyses and meta-regression will be performed to investigate potential sources of heterogeneity. Sensitivity analyses will examine the robustness of the results. Data analysis will be conducted using Comprehensive Meta-Analysis (CMA), version 4. Discussion This review and meta-analysis will be the first to systematically explore and integrate the evidence available on the association between the HEXACO personality traits and SUD and behavioral addictions. By consolidating information, the study will enhance our understanding of the role of personality traits in the development, maintenance, and treatment of SUD and behavioral addictions. Systematic review registration PROSPERO CRD42023468153.